Hybrid Coal: Effects Of Composition And Co-pyrolysis Retention Time in Low Rank Coal and Biomass Waste Co-pyrolysis Process on The Product’s Yield - Jenny Rizkiana; Slamet Handoko; Winny Wulandari; Muhammad Afif Ridha; Hendi Aviano Prasetyo; Dwiwahju Sasongko (Department of Chemical Engineering, Universitas Gadjah Mada, 2018)
Low rank coal upgrading into a more efficient and environmentally friendly fuel can be done through copyrolysis with biomass into a fuel called hybrid coal. The purpose of the research is to determine the effects of biomass composition and copyrolysis retention time to the hybrid coal yields. Copyrolysis process conducted in a vertical tubular fixed bed reactor in an inert condition with atmospheric pressure and temperature set at 300oC. Inert condition achieved by flowing nitrogen gas into the reactor with a flowrate of 1.6 L/minutes. Biomass mixing composition is varied at 20, 30, and 40% from the total weight of the mixture. Copyrolysis retention time varied at 30, 60, and 90 minutes. Hybrid coals are characterized by proximate analysis, ultimate analysis, and calorific value measurement. Increase in retention time of copyrolysis from 30 to 90 minutes causing an increase in calorific value of 12.57-23.80%. From the proximate analysis results, fixed carbon content rise with the increase of co-pyrolysis time. The highest fixed carbon content obtained in the variation of 90 minutes, in the range of 49.36-49.75%. Increasing of sawdust composition from 20 to 40%, lowering the calorific value in the range of 0.58-8.55%.